Aortic valve replacement in over 70- and over 80-year olds: 5-year cohort study. (June 2014) - Wang, Tom Kai Ming; Sathananthan, Janarthanan; Chieng, Nicholas; Gamble, Greg D; Haydock, David A; Ruygrok, Peter N
Background: Demand for aortic valve intervention remains high, and together with the recent introduction of transcatheter aortic valve implantation, this motivates a review of surgical aortic valve replacement in elderly recipients. Methods: Consecutive patients over 70 years of age having isolated aortic valve replacement during 2007–11 were retrospectively identified and divided into 70–79 and ≥ 80 years age groups for analyses. Results: 62 octogenarians and 121 septuagenarians were eligible. Among octogenarians, a lower proportion were in Canadian Cardiovascular Society angina class 3–4 (3.2% vs. 14.0%, p = 0.022) and fewer had diabetes (11.3% vs. 24.8%, p = 0.034), but a higher proportion had infective endocarditis (6.5% vs. 0%, p = 0.012), and EuroSCORE II was higher (4.9% vs. 3.7%, p < 0.001). Despite this, operative mortality was lower in octogenarians (0% vs. 7.4%, p = 0.029), although hospital stay (11.7 vs. 8.9 days, p = 0.026) was longer. One-, 3-, and 5-year survival rates were 95.2%, 90.1%, and 75.3% for octogenarians and 89.2%, 81.7%, and 70.2% for septuagenarians ( p = 0.398). Canadian Cardiovascular Society angina class 3–4 and the presence of other valvular stenosis or regurgitation were independent predictors of mortality. Conclusion: Octogenarians had lower operative mortality despite a higher predicted risk preoperatively. Other factors beyond age and EuroSCORE, such as frailty, may be important in deciding whether elderly patients should undergo aortic valve replacement.